Analisis Strategi Penerapan Digital Marketing dalam Meningkatkan Pendapatan UMKM Keripik Pisang - Rizqul Karimah; Zulviar Anas; Faisol Faisol; , Masruroh Masruroh (JURNAL RISET MANAJEMEN (JURMA), 2026)
The purpose of this study is to describe the strategy of implementing digital marketing to increase the revenue of the Makicha banana chips MSME. This research method uses descriptive qualitative with data collection through interviews, observations, and documentation. The results of this study indicate that the implementation of digital marketing in the Makicha Banana Chips MSME has a positive impact on business development, especially in increasing visibility, market reach, and business revenue. The transition from conventional marketing to the use of social media such as Instagram, WhatsApp, and TikTok is a strategic step in reaching a wider consumer base, including from outside the region. Although the implemented strategy is still simple, such as uploading product photos, testimonials, and sharing information through the story feature, it has been quite effective in attracting consumer interest and increasing the number of orders. However, the implementation of digital marketing is not optimal due to still being constrained by limited human resources, time, and a lack of consistency in content management, so the development of a more structured strategy in content creation is needed. The results of this study are expected to provide an overview for other MSMEs regarding the importance of utilizing social media in expanding the market to increase business revenue.